A selected bibliography on seaweed aquaculture research and development in the Tropical Pacific. - McLachian, J. L. (Pacific Islands Marine Resources Innformation System (PIMRIS), The University of the South Pacific Libirary, 1993)
USP Marine Studies Programme. Technical Report Series; no.1993(6)